PERAN PENDIDIKAN KARAKTER DALAM MENCEGAH PENYELEWENGAN MORAL: STUDI KASUS DI KALANGAN SISWA SEKOLAH DASAR - Mahesty, Naeny; Dwi Lestari, Anita; Novita Fiky Megantari, Elisa; Dwi Lukitoaji, Beny (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2025)
In addition to the cognitive abilities possessed by a student, positive character and morals are also very important and must be possessed and applied by students in their daily lives. Considering the current era, conflicts related to students' character and morals are quite easily encountered. Of course, such conditions are not the desire of all parties, whether it be families, schools, or even the government. This is not merely to create good character in students, but rather to shape a generation of young people who can thrive in community life without harming themselves or others. Of course, the world of education is entrusted with the responsibility by all parties to be able to address this issue. Therefore, this research aims to analyze the role of character education in addressing and preventing conflicts and moral deviations in the environment of elementary school students. Qualitative methods with a case study approach are the research techniques used by the researcher in this study. Where the researcher only focuses on the phenomena and conflicts occurring in the surrounding environment, through the process of data collection in the form of observation and analysis of relevant documents. Thus, the results obtained explain that the role of character education significantly influences the formation of moral behavior in elementary school students. Where character values, such as honesty, responsibility, and empathy, have proven to be quite effective in preventing and addressing issues related to moral deviations. The involvement of a positive environment from parents and schools also greatly influences the strengthening of character education through its implementation in students' lives. It is hoped that these findings can contribute to the development of the education curriculum, which focuses on the formation and implementation of good character values for elementary school students.